KOMUNIKASI DALAM KEGIATAN PUBLIC RELATIONS - Sumarto, Rumsari Hadi (Informasi, 2016)
Organizations in maintaining the sustainability of life requires communication. Good established communication will affect the harmonious and harmony relations between the organization and its publics. A positive image is represented if there is a harmonious interaction between an organization and its publics. Imaging of anorganization is usually attached to public relations. Imaging can be awakened/built if there is a harmonious and pleasant communication between an organization and its publics. To support public relations activities, organization requires communication to be able to interact with the public in two-way communication. A PR practitioner should be able to make other people understand the message delivered so as to create mutual symbiosis between the two parties. Thus, the impression captured by the public is a positive impression of the organization. Public relations also allows feed back to the public so that the public can freely response the message from the organization and express what they want and what they complaint. The public response will be followed up so that the public will be satisfied on what the organization done to the public. Public relations is also constantly evaluating so that public opinion can be well controlled. Thus, public relations is an activity which essentially directs the organization to gain public recognition. Further public relations stride motion seeking to form public opinion that benefit the organization so that a positive image of the public will be given to an organization. Organisasi akan tetap langgeng saat terbangun komunikasi yang baik. Komunikasi yang baik akan mempengaruhi hubungan yang harmonis dan selaras antara organisasi dan publiknya. Sebuah citra positif terbangun jika ada interaksi yang harmonis antara organisasi dan publiknya. Untuk mendukung kegiatan public relations, organisasi membutuhkan komunikasi dua arah. Seorang praktisi PR harus mampu membuat oranglain memahami pesan yang disampaikan sehingga tercipta simbiosis antara kedua belah pihak. Dengan demikian, kesan yang ditangkap oleh masyarakat adalah kesan positif dari organisasi. PR juga memungkinkan umpan balik kepada publik sehingga masyarakat dapat dengan bebas mendapat pesan dari organisasi dan mengekspresikan apa yang mereka inginkan dan apa yang mereka keluhan. PR juga perlu terus mengevaluasi sehingga opini publik dapat dikontrol dengan baik. Dengan demikian, PR adalah kegiatan yang pada dasarnya mengarahkan organisasi untuk memperoleh pengakuan publik. PR berusaha untuk membentuk opini publik yang menguntungkan organisasi sehingga citra positif terbangun dengan sendirinya.